2022
DOI: 10.4018/978-1-6684-5129-8.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Biological Applications

Abstract: Essential oils are terpinoids and their oxygenated derivatives, which are widely used for antimicrobial, fungicidal, antiparasitical, insecticidal uses. They are aromatic, hydrophobic, and volatile in nature and frequently used in medicinal and cosmetic industries. Especially nowadays, volatile oils have a significant role in pharmaceutical, sanitary, cosmetic, agricultural, and food industries. Various conventional and modern methods of extraction of volatile oil are available. Volatile oil can play an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Monoterpenes are a terpene type that consists of two isoprene units and has the molecular formula of C 10 H 16 ( Sundriyal, 2022 ). Studies by various researchers have also reported that monoterpenes have antiseptic, anti-cancer, antibacterial, and antifungal properties ( Scariot et al., 2021 ; Silva et al., 2021 ).…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…Monoterpenes are a terpene type that consists of two isoprene units and has the molecular formula of C 10 H 16 ( Sundriyal, 2022 ). Studies by various researchers have also reported that monoterpenes have antiseptic, anti-cancer, antibacterial, and antifungal properties ( Scariot et al., 2021 ; Silva et al., 2021 ).…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…It belongs to the class of compounds known as sesquiterpenes, which occur naturally in plants and have diverse biological activities [40]. Caryophyllene has been found to have a range of biological activities, including anti-inflammatory, antioxidant, and anticancer properties [41]. One of the most remarkable properties of caryophyllene is its ability to operate as a selective agonist of cannabinoid receptor type 2 (CB2) [42].…”
Section: Caryophyllenementioning
confidence: 99%
“…EOs are mainly extracted by distillation, but there are other techniques such as cold extraction, supercritical carbon dioxide, and ultrasonic- or microwaveassisted extraction [ 19 ]. EOs are generally liquid at room temperature, volatile, flammable, and fragrant, and have a density generally less than one [ 20 ]. Some EOs have a characteristic color, such as blue tansy, red-brown cinnamon, or green Inula.…”
Section: Introductionmentioning
confidence: 99%